2015
DOI: 10.1371/journal.pone.0132511
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Biopsy for the Head and Neck Using Contrast-Enhanced Ultrasonography Combined with Indocyanine Green Fluorescence in Animal Models: A Feasibility Study

Abstract: BackgroundSentinel node navigation surgery is gaining popularity in oral cancer. We assessed application of sentinel lymph node navigation surgery to pharyngeal and laryngeal cancers by evaluating the combination of contrast-enhanced ultrasonography and indocyanine green fluorescence in animal models.MethodsThis was a prospective, nonrandomized, experimental study in rabbit and swine animal models. A mixture of indocyanine green and Sonazoid was used as the tracer. The tracer mixture was injected into the tong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…To review contrast-enhanced lymphosonography in OSCC, a systematic literature search was conducted, which led to retrieval of 107 PubMed indexed articles. A total of 6 studies were considered relevant (i.e., 2 clinical studies [ 34 , 35 ] and 4 large animal studies [ 82 , 83 , 84 , 85 ]). Cross-reference did not lead to identification of additional relevant articles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To review contrast-enhanced lymphosonography in OSCC, a systematic literature search was conducted, which led to retrieval of 107 PubMed indexed articles. A total of 6 studies were considered relevant (i.e., 2 clinical studies [ 34 , 35 ] and 4 large animal studies [ 82 , 83 , 84 , 85 ]). Cross-reference did not lead to identification of additional relevant articles.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, none of the studies in humans or large animals found HEN enhancement [ 34 , 35 , 82 , 83 , 84 , 85 ]. It is possible that this is prevented by phagocytosis of microbubbles (which was histologically confirmed in animals for Sonazoid [ 85 ]) and the size of microbubbles compared to small-molecule dyes. Another advantage is the possibility to use lymphosonography preoperatively to improve lymph node selection for USgFNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a verification bias may exist because patients with benign cytopathologic results and follow‐up for at least 12 months were considered negative. Second, several novel US techniques, such as real‐time or shear wave elastography and contrast‐enhanced ultrasonography, were not assessed, and their adaptation may improve this prediction model in the future. Third, we did not compare that if there were differences in criteria between different head and cancers in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of contrast-enhanced ultrasound and fluorescence imaging for the intraoperative detection of sentinel lymph nodes is a new development in the field of visualization techniques [38] . Contrast-enhanced ultrasound alone could potentially detect radiation-induced changes in the carotid arteries at an early stage, offering modulation of the local radiation dose [28] .…”
Section: Future Perspectivesmentioning
confidence: 99%